2017
DOI: 10.1161/jaha.117.005710
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Elevated Pulse Pressure and High Resting Coronary Blood Flow Velocity in Patients With Angiographically Normal Epicardial Coronary Arteries

Abstract: BackgroundThe aim of our study was to evaluate the relationship of pulse pressure (PP), a raw index of arterial stiffness, with noninvasively determined coronary flow reserve (CFR) and its components, in patients with angiographically normal epicardial coronary arteries.Methods and ResultsThe study population included 398 patients without angiographic evidence of coronary stenosis, who underwent high‐dose dipyridamole stress echocardiography with transthoracic‐derived CFR evaluation on the left anterior descen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 62 publications
3
15
0
Order By: Relevance
“…This study examined transthoracic-derived CFR in a study population of 398 patients. However, the resting coronary flow velocity, and not the CFR, was significantly associated with PP and only on multiple linear regression analysis, at that 9. Other echo-based studies have also demonstrated that arterial stiffness is inversely related to CFR or hyperaemic coronary flow velocity in patients with non-obstructive CAD 7–9.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…This study examined transthoracic-derived CFR in a study population of 398 patients. However, the resting coronary flow velocity, and not the CFR, was significantly associated with PP and only on multiple linear regression analysis, at that 9. Other echo-based studies have also demonstrated that arterial stiffness is inversely related to CFR or hyperaemic coronary flow velocity in patients with non-obstructive CAD 7–9.…”
Section: Discussionmentioning
confidence: 86%
“…9 Other echo-based studies have also demonstrated that arterial stiffness is inversely related to CFR or hyperaemic coronary flow velocity in patients with nonobstructive CAD. [7][8][9] Previous studies used transthoracic echocardiography to measure coronary flow and velocity, and recruited a relatively small number of participants. These studies did not measure invasive aortic BP.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…[76] ESC/ESH guidelines propose the carotid-femoral pulse wave velocity (PWV) as the gold standard to assess arterial stiffness [6,77]: the stiffer the arteries, the higher the PWV. Therefore, correctly diagnosing and treating patients at the beginning of the disease could prevent this further complication by limiting the aortic damage [78][79]. However, this tool is not currently used in the clinical practice.…”
Section: Aortamentioning
confidence: 99%